Implementation of Transparency and Accountability in Financial Management of Village Fund Allocation in 2022 in Pandai Village, Woha District, Bima District - Nasrullah Nasrullah; Abdul Muttalib; Kahar Kahar; Ari Anggareksa (Jurnal Ilmu Manajemen Profitability, 2024)
This research is a type of qualitative research which aims to explore the implementation of transparency and accountability in the financial management of Village Fund allocations (ADD) in Pandai Village, Woha District, Bima Regency, in 2022. In the context of regional autonomy, the village government has the responsibility to independently manage the resources and funds provided to improve development and welfare of the community. This research uses primary and secondary data, with data collection techniques in the form of observation, interviews and documentation. The research results show that Pandai Village has implemented the principles of accountability and transparency in all stages of ADD management, from planning to reporting. The application of the accountability principle involves responsibility and reporting, which has been implemented through an online system and monthly accountability reports submitted to the relevant agencies. This process involves all relevant agencies, the Village Consultative Body (BPD), and the village community. In the aspect of transparency, Pandai Village actively involves the community in planning through village meetings, where community participation is highly valued. In addition, the implementation of physical and non-physical activities funded by ADD is made open through information boards, billboards and quarterly accountability placed in front of the village office. The Pandai Village community is actively involved in every stage, from village deliberations to evaluating the implementation of activities. Thus, Pandai Village has succeeded in implementing transparency and accountability in ADD management, creating community involvement, and providing clear information regarding the use of village funds. The application of these principles is an important basis for realizing good governance at the village level..